Ingénierie didactique coopérative : quelle pratique de collaboration entre professeurs et chercheurs ? - Mireille Morellato (Université de Provence, 2019)
We seek to describe the cooperative practices of a team of teachers and researchers during the implementation of a cooperative didactic engineering on the construction of number concepts for 6-year-old and 8-year-old pupils (first & second grades). The collective group founded by teachers and researchers are viewed as an institution within the research project Ace-arithmécole, with a specific dialogue, that of the engineering dialogue of the project. We analyse this dialogue through an emblematic example. We use the Joint Action Theory in Didactics. We refer to the notion of the dialectic of contract / milieu in order to identify the transactions between the collective members from a didactic point of view. We show how experience-facts have been developed by these transactions, that is to say facts that have been learnt from the collective, lived experience. They are the result of a common investigation of the didactic engineering. Thanks to this collective experience, each member is in a position to take on a share of the construction of the engineering knowledge.